AN INDEPENDENT TAXATION AUTHORITY IN THE FORM OF A STATE REVENUE AGENCY IN A STUDY - Rahutama Yusuf Ardiansyah (Journal of Accounting Issues, 2023)
In an evolving global context, the need for a State Revenue Agency separate from the Ministry of Finance is increasingly urgent. This separation of functions will provide a strong foundation in improving the state revenue system and the management of state finances, and reduce the risk of corruption and misuse of state finances. Therefore, immediate steps should be taken to establish an independent State Revenue Agency to meet the increasingly complex challenges and demands of the times. Several theories support the establishment of an independent tax and revenue authority. Agency principle theory explains the importance of separating tax functions from other government agencies to avoid conflicts of interest and ensure efficient tax collection. Public choice theory also underlines the need for an independent authority to prevent political intervention that could potentially harm the public interest. The research method which includes literature study, comparative analysis, interviews, qualitative analysis, and normative approach will provide a comprehensive understanding of independent tax and revenue authorities and their implications in state financial management. Despite difficult challenges and obstacles, the establishment of an independent revenue agency authority remains possible with strong political support, consensus, and commitment to improving transparency, accountability, and efficiency in the management of state finances. In conclusion, the independence of tax and revenue authorities plays a crucial role in the management of state finances. Efficiency, transparency, accountability, and public trust are the main benefits that can be gained from this independence. Although there are challenges in implementing it, measures to separate the taxation function from political interference and other parties' interests should be championed to ensure optimal state revenue collection and fair distribution of the tax burden for all citizens.